INCOME INEQUALITY AND SOCIAL WELFARE: IMPACT ANALYSIS OF REDISTRIBUTION POLICIES IN DEVELOPING COUNTRIES - Loso Judijanto; Syaiful Pakaya; Bahrun Thalib; Harlina Kurniaty; Sunarmie (CV. Adiba Aisha Amira, 2025)
Income inequality is a pressing issue in developing countries, with far-reaching consequences for social welfare. This study examines the impact of redistribution policies on income inequality and social welfare in the context of developing nations. We analyze various policies, including progressive taxation, social safety nets, and direct cash transfers, and assess their effectiveness in reducing income disparities. Case studies from countries like Brazil and South Africa provide valuable insights into successful redistribution programs. Additionally, we explore the challenges and limitations of such policies, including fiscal constraints, corruption, and political resistance. Our findings reveal that well-designed redistribution policies can significantly reduce income inequality, improve access to education, enhance healthcare, and reduce poverty. However, we also highlight the trade-offs and unintended consequences associated with these policies. By understanding the intricate relationship between income inequality and social welfare, this research aims to provide policymakers with valuable insights and recommendations to create more equitable and prosperous societies.